New species of Chaetonerius Hendel (Diptera: Neriidae) and key for identification of the Neriidae of Tanzania - Sepúlveda, Tatiana A.; Echeverry, Angela; Souza, Diego De S. (Zootaxa, 2020)
Chaetonerius Hendel is the only native genus of Neriidae from the African continent, with 21 species described. Although widely distributed across the Afrotropical region, the species of Chaetonerius are still poorly known and recent efforts are being devoted to clarify the taxonomy of the family and discover its diversity. Here, we describe a new neriid species from Tanzania, Chaetonerius stichodactylus sp. n. Illustrations of the male holotype, including the external and internal genitalia, are presented and a key for the species of Neriidae of Tanzania is provided.